Detection of Southern tomato virus by molecular hybridisation. (27th June 2017) - Puchades, A.V.; Carpino, C.; Alfaro‐Fernandez, A.; Font‐San‐Ambrosio, M.I.; Davino, S.; Guerri, J.; Rubio, L.; Galipienso, L.
Abstract: Southern tomato virus (STV) is a double‐stranded RNA (dsRNA) virus belonging to the genus Amalgavirus from the family Amalgamaviridae . STV has been detected in tomato plants showing symptoms of stunting, fruit discoloration and size reduction, although its role on symptom development is unclear. Also, little is known about the incidence and epidemiology of this virus and how it spreads in tomato crops. In this work, we developed a molecular hybridisation method by using a digoxigenin‐labelled RNA probe based on the nucleotide sequence of the STV putative coat protein which was tested with different procedures for preparation of plant material. This technique was sensitive enough to detect STV from sap extracts (obtained just by grinding in buffer) from different plant tissues such as leaves, fruits, roots and seeds. This procedure is suitable for field surveys since it allows a cheap and quick processing of a high number of samples. Surveys performed in three important tomato production areas (Peninsular Spain, the Canary Islands and Sicily) showed that STV is widely spread, with incidences ranging from 18% to 74% in different local and commercial tomato varieties.